Effect of Media Exposure on Social Development in Children - Sung Koo Kim MD, PhD; Da Som Wi MD; Kyung Mi Kim MA (SAGE Publishing, 2023)
Purpose The prevalence of autism spectrum disorder in children, who show problems in social development, is increasing rapidly. If children watch media at an early age, they lose the time to interact with their parents and will not be able to play creatively, which can have a negative impact on social development. This study was performed to evaluate the association of media exposure with social developmental delay. Methods The sample consisted of 96 patients with social developmental delay who visited the developmental disorder clinic from July 2013 to April 2019. The control group included 101 children who visited our developmental clinic with normal developmental screening test results during the same period. The data were collected using self-reported questionnaires with questions regarding media exposure time, content, background media or foreground media, the age of first exposure, and media exposure with or without parents. Results In regard to media exposure time, 63.5% of the social developmental delay patients were exposed to media for more than 2 hours a day compared to 18.8% of the control group ( P  < .001, [OR] = 8.12). In the risk factor analysis of media exposure on social development, male gender, media exposure before 2 years of age, exposure for more than 2 hours, and exposure alone without parents were statistically significant. Conclusion Media exposure was a significant risk factor for social developmental delay.